The concept of financial literacy in the research of Ivan Prokopenko and foreign experts - Vlasenko, Y. (New Collegium, 2022)
The article is devoted to the disclosure of the essence of financial literacy as a key competence of a modern young person through the prism of the professional development of Ivan Prokopenko and foreign specialists. The research used methods – comparative historical, analysis, synthesis. In the article, the author revealed the key concept as a person's ability to understand and use financial skills, including managing personal finances, budgeting and investing, understanding certain financial principles and concepts such as: time value of money, compound interest, debt management and financial planning. The author noted in the article that Ivan Prokopenko paid considerable attention to the formation of students' financial literacy, the implementation of European standards of understanding and technologies for the formation of this competence. It is also stated that in the context of the formation of personal financial literacy in the educational process, I. Prokopenko stood for the positions of people-centeredness and a systemic approach. In developing the issue of meaningful and methodical support, the academician oriented the applicants to the formation of the ability to make conscious financial decisions. In this regard, issues of social and economic security, financial independence became crucial. This vision became the basis for the implementation of the initiative to introduce an individual learning trajectory for students of different levels of education at the G. S. Skovoroda Kharkiv National Pedagogical University The comparative analysis made it possible to distinguish the worldview target component, the practical competence component, and the strategic subject component in the content of the studied concept. In the research work of I. Prokopenko, U. Baitsakhan, M. Demertzis, A.T. Pasha, H. Picatosta, E.M. Hergins are expressive in their outlook on the target component. We see the study of global and national experience of financial literacy formation in force majeure conditions, when situations of uncertainty affect national and global economic systems, as a promising direction for further scientific research